Sосial-Есоnоmiс Dеvеlоpmеnt and Its Philоsоphiсal Еssеnсе - Khоlоv Shеrali Akhrоrbоyеviсh (Journal of Regional Economics and Development, 2025)
This study explores the philosophical and socio-economic dimensions of economic development, emphasizing the necessity of integrating social progress with economic growth for a sustainable and inclusive model. The research employs a qualitative approach, analyzing theoretical frameworks and historical data to assess the role of innovation, technological advancements, and structural changes in national economies. Findings indicate that economic growth alone does not guarantee societal well-being, as it must be complemented by investments in human capital, education, and institutional frameworks. Furthermore, structural transformations, such as shifts from agrarian to industrial and service-based economies, play a crucial role in long-term sustainability. The study highlights that political stability, social cohesion, and equitable resource distribution are essential factors in fostering economic development. The paper concludes that economic policies should prioritize both quantitative expansion and qualitative improvements to ensure holistic national progress.